2019
DOI: 10.1155/2019/9681424
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Outcomes of Two-Level PELD and Foraminoplasty PELD for Highly Migrated Disc Herniations: A Comparative Study

Abstract: Objective The aim of this study is to compare the clinical outcomes of two-level percutaneous endoscopic lumbar discectomy (PELD) and foraminoplasty PELD in treating highly migrated lumbar disc herniations. Methods Patients with highly migrated lumbar disc herniations were enrolled from May 2014 to June 2016. Low back pain and leg pain were evaluated by the Visual Analog Scale (VAS), and functional outcomes were assessed with the Oswestry Disability Index (ODI). The satisfaction rate of clinical outcomes was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“… 29 , 31 , 33 It should be noted that the target location, limited possibility of endoscopic adjustment, and risks of dural tears and incomplete removal of the herniated disc may limit the application of these methods. 29 , 31 , 33 Two-level PELD techniques such as the transforaminal approach alone or in combination with an interlaminar approach reduce the incidence of postoperative nucleus pulposus residue, 30 , 32 but these procedures are cumbersome, have a long operative time, and cannot be used for L5–S1 far-migrated LDH. 29 , 32 The results of our study show that sciatica in both the IELD and IMLD groups significantly improved and remained satisfactory at the 24-month follow-up, indicating that adequate decompression was achieved, which is in accordance with other published reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 , 31 , 33 It should be noted that the target location, limited possibility of endoscopic adjustment, and risks of dural tears and incomplete removal of the herniated disc may limit the application of these methods. 29 , 31 , 33 Two-level PELD techniques such as the transforaminal approach alone or in combination with an interlaminar approach reduce the incidence of postoperative nucleus pulposus residue, 30 , 32 but these procedures are cumbersome, have a long operative time, and cannot be used for L5–S1 far-migrated LDH. 29 , 32 The results of our study show that sciatica in both the IELD and IMLD groups significantly improved and remained satisfactory at the 24-month follow-up, indicating that adequate decompression was achieved, which is in accordance with other published reports.…”
Section: Discussionmentioning
confidence: 99%
“…Although the incidence of complications was higher with the latter, no major complications occurred. Modified PELD techniques have been used to treat farmigrated LDH, with good clinical results; 20,22,[29][30][31][32][33] However, these methods have various shortcomings and limitations. Several studies have reported good clinical results in more than 90% of patients with far-migrated DH treated by PETLD, but it is difficult to directly view the distal free nucleus pulposus due to obstruction of the facet joint and pedicle, especially as the far-migrated disc is often separated into many fragments.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al. reported 26 cases of VHMDH using the foraminoplasty endoscopic technique and obtained a 92.3% satisfactory rate [ 27 ]. In addition to the establishment of a widened foraminal working window, the choice of puncture point and direction also ultimately determines whether TELD treatment will be successful.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al, 2019 reported pelD as an exopolysaccharide transporter. 51 This could explain the trial of the cell to abrogate the transformation from the biofilm form by up-regulation of the exopolysaccharide synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PeLG has shown to have a catalytic activity as a degrader of ePsl in the extracellular matrix, so consistently, it will cause an exopolysaccharide degradation. 51 Byrd et al, 2009 showed overlapping of the enzymatic roles in the biosynthesis of Psl, LPS production, and the part of Psl genes in surface conditioning and attachment. These results aroused an amending trial of Pseudomonas to transform into a planktonic state to render the inhibitory effect of honey.…”
Section: Discussionmentioning
confidence: 99%